2012
DOI: 10.1097/fbp.0b013e32835a5184
|View full text |Cite
|
Sign up to set email alerts
|

Low maternal care exacerbates adult stress susceptibility in the chronic mild stress rat model of depression

Abstract: In the present study we report the finding that the quality of maternal care, in early life, increased the susceptibility to stress exposure in adulthood, when rats were exposed to the chronic mild stress paradigm. Our results indicate that high, as opposed to low maternal care, predisposed rats to a differential stress-coping ability. Thus rats fostered by low maternal care dams became more prone to adopt a stress-susceptible phenotype developing an anhedonic-like condition. Moreover, low maternal care offspr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…In the ELA group, all 10 animal studies examining GR gene methylation investigated exon 1 7 , and 7 studies (70%) reported a significant increase in methylation in the exon 1 7 promoter, while three studies reported no change in exon 1 7 methylation status (22, 33, 36). Of the 10 human studies examining exon 1 F methylation, 9 reported increased promoter methylation with ELA (90%).…”
Section: Resultsmentioning
confidence: 99%
“…In the ELA group, all 10 animal studies examining GR gene methylation investigated exon 1 7 , and 7 studies (70%) reported a significant increase in methylation in the exon 1 7 promoter, while three studies reported no change in exon 1 7 methylation status (22, 33, 36). Of the 10 human studies examining exon 1 F methylation, 9 reported increased promoter methylation with ELA (90%).…”
Section: Resultsmentioning
confidence: 99%
“…However, in another study, early deprivation was reported to increase the acquisition of LH by adult rats of the Fischer strain (but not by Wistar rats), but the effect was reversed by chronic fluoxetine treatment, suggesting that this will not lead to a model for antidepressant resistance (Rüedi-Bettschen et al 2004). A third study reported that naturalistically occurring poor maternal care led to an increased anhedonic response to CMS in outbred Wistar rats; the response to antidepressant treatment was not examined (Henningsen et al 2012). However, there is evidence that greater adult emotionality between mouse strains may to some extent reflect differences in early maternal care (Calatayud and Belzung 2001), and this is not associated with resistance to antidepressant treatments ).…”
Section: Early Life Stressmentioning
confidence: 94%
“…Changes in maternal behavior were suggested as the key factor underlying long-term effects of early maternal separation for different duration on the offspring behavior [48]. This hypothesis was supported by a strong correlation between the levels of maternal care and the behavior of adult offspring [49, 50]. Though the exact mechanisms linking early environmental conditions and offspring behavior in adulthood through changes in maternal care remain unclear, these effects are accompanied by important changes in central levels of BDNF [49].…”
Section: Interference Into Early Life Developmentmentioning
confidence: 99%